PERGESERAN PARADIGMA DAN PERSEPSI KARYA ARSITEKTUR BAGI ARSITEK DI ERA INFORMASI - Prihastomo, Bondan (Universitas Aisyiyah Yogyakarta, 2018)
Abstract: In the course of time, an architectural work always undergoes a change of perception, both by the general public and among architectural practitioners. In the digital age, this is quite important. This is related to technological advances that are able to provide convenience to the designer to create an architectural masterpiece. Some architectural works have an unfinished value, because it has only one aspect of value only, that is most of the visual aspect.Keywords : paradigm, persepsi, arsitektur, arsitek, era informasi